Efficacy, safety, and patient acceptability of the combined chlormadinone acetate-ethinylestradiol oral contraceptive - Serena Ferrari; Marianna Cannoletta, Matteo Generali; et al (Dove Medical Press, 2010)
Serena Ferrari, Marianna Cannoletta, Matteo Generali, Lucia Cazzato, Angelo CagnacciDepartment of Obstetrics, Gynecology, and Pediatrics, Azienda Ospedaliero, Universitaria di Modena, ItalyAbstract: Since their introduction in 1959, development of hormonal contraceptives has been ongoing, with the ultimate aim of creating not only an effective and safe contraceptive method, but also a drug able to meet the need for treatment of other conditions, such as acne, seborrhea, and hirsutism, with few or no side effects. With this objective, a new progestin, chlormadinone acetate (CMA), has been developed as a derivative of progesterone for contraception. This new molecule has been introduced in combination with ethinylestradiol (EE) 30 µg as a safe contraceptive with antiandrogenic properties. Many clinical studies have investigated this new oral combination and found it to be safe, with a Pearl Index similar to that of other combined hormonal contraceptives. CMA, because of its antiandrogenic properties, has been also considered effective for resolution of acne, seborrhea, and hirsutism. The data show it to be a safe molecule in terms of glucose and lipid metabolism. No major weight changes have been linked with its use, and it seems to be the only progestin able to reduce fat mass during use. The CMA-EE combination is well tolerated and acceptable to women. Adverse events related to its use are similar to those reported with other third-generation contraceptives. We can conclude that CMA-EE is an effective, safe, and well tolerated antiandrogenic hormonal contraceptive.Keywords: chlormadinone acetate, acne, weight, metabolism, safety, hormonal contraceptive